Treatment of Molar-incisor Hypomineralization: A Case Report of 11-year Clinical Follow-up - Vieira, Apm [UNESP]; Emerenciano, N. G. [UNESP]; Moda, M. D. [UNESP]; Silva, Úae [UNESP]; Fagundes, T. C. [UNESP]; Danelon, M. [UNESP]; Cunha, R. F. [UNESP] (Operative Dentistry, 2023)
The purpose of this case report was to describe an 11-year follow-up of a patient presenting with molar-incisor hypomineralization (MIH) having yellowish and porous permanent incisors and molars. Clinical examination revealed demarcated brown opacities on one upper and one lower central incisor and three first permanent molars. Initially, treatment involved oral hygiene and periodic fluoride varnish application. Subsequently, the occlusal surfaces of the affected molars were restored or sealed with glass ionomer cement. At-home dental bleaching was also performed. Areas of unsatisfactory esthetics on the incisors were replaced by composite resins. This report discussed the patient's needs and expectations, the difficulties of prolonged treatment for patients with MIH, and the restorative protocol involving at-home dental bleaching and composite resins.